2009
DOI: 10.1097/ajp.0b013e31817d105e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tobacco Use in Patients Presenting to a Multidisciplinary Outpatient Treatment Program for Fibromyalgia

Abstract: Current tobacco use was associated with more severe fibromyalgia symptoms in patients presenting to a specialized fibromyalgia treatment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 43 publications
9
55
1
8
Order By: Relevance
“…Among negative factors related to modulating disease progression or clinical features of FMS, environmental triggers such as trauma, emotional stress, infection or vaccination, and diverse autoimmune diseases have been reported by several clinical investigations [12][13][14]. Recently, some studies have suggested that smoking could influence pain severity or functional features in FMS [15][16][17]. In contrast, a recent study from a Brazilian group showed no impact of smoking on the health status of FMS patients [18].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Among negative factors related to modulating disease progression or clinical features of FMS, environmental triggers such as trauma, emotional stress, infection or vaccination, and diverse autoimmune diseases have been reported by several clinical investigations [12][13][14]. Recently, some studies have suggested that smoking could influence pain severity or functional features in FMS [15][16][17]. In contrast, a recent study from a Brazilian group showed no impact of smoking on the health status of FMS patients [18].…”
Section: Introductionmentioning
confidence: 76%
“…A majority of the research has suggested that smoking could influence clinical features and functional impairment in FMS patients [15][16][17]. However, no association between smoking and FMS features was proposed in a clinical study of the Brazilian FMS population [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous findings that have found fibromyalgia more likely to be diagnosed in female patients 41 ; however, there is a paucity of research regarding the association between this pain condition and health behaviors. A study by Weingarten and colleagues examined the prevalence and correlates of cigarette smoking in a sample of 984 individuals evaluated at a multidisciplinary fibromyalgia clinic, with smoking status reported to be associated with greater disease severity 42 . Previous research has also examined the role of excess weight in patients diagnosed with fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%